The impact of governance on export performance in Asian countries: empirical evidence - Jama, Abdikarim Bashir (2019)
Export plays a magnificent role in economic development and integration of countries by trading each other whereby it facilitates the free movement of goods and services from one country into another. While governance indicators can be considered the main tool that supports such activity. This study investigates the impact of governance on the export performance of South East Asia countries. The performance of export is measured by the proxy of export value as the dependent variable. This study uses three (3) independent variables derived from six World Governance Indicators (WGI) namely: regulatory quality (RQ), political stability (PS), voice and accountability (VA). While control variables refer to macroeconomic factors that relate trade includes the real effective exchange rate (REER) and the labor force participation rate (L). The data is limited to the export of Southeast Asia countries within the period of 2008 until 2017. This study analyses using fixed-effect models (FEM). The results show that voice and accountability has a positive and significant effect on export performance. However, regulatory quality has a negative and statistically significant impact on export performance. Also, political stability has a positive but no significant influence on export performance. This study also found both real effective exchange rate and labor force participation rate have a negative and statistically significant impact on export performance. The findings suggest that governance indicators play a significant role in economic development particularly the trade openness, therefore, it's substantial for South East Asia countries to engage more economic integration policy to enhance export performance. Also, this study has strongly contributed to the existing literature of cross country export analyses particularly in the context of Southeast Asia countries.